PENINGKATAN KREATIVITAS GURU SEKOLAH DASAR MELALUI PELATIHAN MEMBUAT DISPLAY KELAS - Nurul Aliza; Mia Kusumawati; Domi Bustomi (An-Nizam, 2023)
Teachers are professional teaching staff who carry out the task of educating the next generation of the nation. In addition to educating, teachers are also required to be creative in teaching and learning activities and in managing the class. The teacher's creativity in managing the class can affect learning motivation and student learning outcomes. Good classroom management can create conducive classroom learning activities. To overcome the problem of the lack of creativity of elementary school teachers, training was held to make Class Displays. This training activity was attended by 10 teachers from an elementary school located in Karangsegar Village. The method used in the training activities for making Class Displays conducted at SDN Karangsegar 01 is by conducting outreach related to Class Displays to elementary teachers by providing knowledge about the meaning, purpose and benefits of Class Displays, then providing training on making Class Displays. The purpose of the Class Display making training is to provide motivation, understanding and skills for Elementary School teachers in making creative Class Displays. The results of the Training on Making Class Displays, including teachers understanding Class Displays, increasing teacher creativity in class displays and helping to increase student enthusiasm in class learning.